2010
DOI: 10.1007/s00586-010-1538-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous ossification of the posterior longitudinal ligament and ossification of the ligamentum flavum causing upper thoracic myelopathy in DISH: case report and literature review

Abstract: A rare case of a 44-year-old Chinese male with diffuse idiopathic skeletal hyperostosis (DISH) and simultaneous ossification of the posterior longitudinal ligament (OPLL) and ossification of the ligamentum flavum (OLF) at T1-2 causing thoracic myelopathy is reported herein. Posterior decompression without extirpating the OPLL was performed at T1-2. Postoperatively, symptoms were greatly improved, with remaining hyperreflexia and Grade 4/5 muscle strength in the lower extremities. The Japanese Orthopedic Associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…DISH is an asymptomatic condition in general; however, it can present with neurological symptoms due to compression of the spinal cord. Qunfeng et al (4) reported neurological deficits due to OPLL and OLF causing spinal cord compression associated with DISH. Reisner and Wilson also reported that OLF associated with DISH had an important role in the development of neurologic deficits, mainly in the thoracic spine (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DISH is an asymptomatic condition in general; however, it can present with neurological symptoms due to compression of the spinal cord. Qunfeng et al (4) reported neurological deficits due to OPLL and OLF causing spinal cord compression associated with DISH. Reisner and Wilson also reported that OLF associated with DISH had an important role in the development of neurologic deficits, mainly in the thoracic spine (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…DISH mostly occurs in males and in the fifth decade of the life and may be associated with systemic diseases, such as diabetes mellitus and obesity (2). The anterior longitudinal ligament is the primary site of involvement in DISH; however, ossified posterior longitudinal ligament (OPLL) and ossified ligamentum flavum (OLF) have been also described in DISH patients (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…This abnormality appears to be higher in the middle-aged men than women [1]. DISH is rarely accompanied with Ossification of the Posterior Longitudinal Ligament (OPLL) and Ossification of the Ligamentum Flavum (OLF) [2]. OPLL characterized by calcification of the posterior longitudinal ligament [3] leads to cord compression [3].…”
Section: Background and Importancementioning
confidence: 99%
“…[1][2][3][4][5][6][7] We describe a case of cervical myelopathy secondary to OPLL and OLF that required surgery. Patients are usually treated with cervical laminectomy or laminoplasty with JOSS CASE REPORT [1][2][3] …”
Section: Introductionmentioning
confidence: 99%